Michel Foucault: Influence of Discipline on Personality - Stančienė, Dalia Marija (Problemos, 2006)
Michel Foucault genealogically inquires the process of the alienation of sovereign personality and the role of disciplinary institutions in it. He focuses attention on the development of these institutions, on their bureaucratic (anonymous) functioning and influence over personality by specific coercive forms and procedures aimed at making a person useful to society as much as possible. In this process, the cooperation of the institutions of knowledge and power is extremely important. They cooperate in giving social and personal identity to man, in transforming the subject into the object and separating it from itself as well as from others. While analyzing these phenomena Foucault exposes the methods by which people, influenced by disciplinary institutions, act on their own bodies, souls, way of thinking and behavior. He underlines that the standardization and socialization of personality is mostly performed in educational, medical and penitentiary institutions. In the opinion of the author, Foucault’s approach to the analysis of person-society relation detects the criteria of „morality“ of governance.